Cohen's pathways of the pulp - Hargreaves, Kenneth M.; Cohen, Stephen, 1938-; Berman, Louis H. (St. Louis, Mo. : Mosby Elsevier, 2011)
'Completely updated to keep you absolutely current, this comprehensive reference remains the definitive text for the classroom and clinical practice. The tenth edition offers a superb full-color design and integrates the latest evidence-based research for clinical treatments. It includes coverage from preparing the clinician and patient for endodontic treatment to the role an endodontist can play in the treatment of traumatic injuries, to the procedures used in the treatment of both pediatric and older patients. Providing the latest in treating endodontic infections and pain, and in establishing differential diagnoses, this is a one-stop resource!'--BOOK JACKET.
Microbiology and treatment of endodontic infections / JosF. Siqueira, Jr. and Isabela N. R{u3BF0}cas -- Regenerative endodontics / Kenneth M. Hargreaves and Alan S. Law -- The role of endodontics after dental traumatic injuries / Asgeir Sigurdsson, Martin Trope, and Noah Chivian -- Endodontic and periodontal interrelationships / David G. Kerns and Gerald N. Glickman -- Endodontic pharmacology / Karl Keiser and B. Ellen Byrne -- Local anesthesia in endodontics / Al W. Reader, John M. Nusstein, and Kenneth M. Hargreaves -- Periradicular surgery / Bradford R. Johnson, Mohamed I. Fayad, and David E. Witherspoon -- Restoration of the endodontically treated tooth / Didier Dietschi, Serge Bouillaguet, and Avishai Sadan -- Pediatric endodontics : endodontic treatment for the primary and young permanent dentition / Paula J. Waterhouse ... [et al.] -- Effects of age and systemic health on endodontics / Carl W. Newton and Jeffrey M. Coil -- Nonsurgical retreatment / Robert S. Roda and Bradley H. Gettleman -- Understanding and managing the fearful dental patient / Henrietta L. Logan -- The law and dental technology : focus on endodontics / Arthur W. Curley -- Digital technology in endodontic practice / Martin D. Levin -- Cone beam imaging for endodontic procedures / Dale A. Miles and Thomas V. McClammy -- Key principles of endodontic practice management / Roger P. Levin.
Rev. ed. of: Pathways of the pulp. c2006.
This book inclueds online access, please refer to library staff for the password.
Includes bibliographical references and index.
Keywords: Dental Pulp; Endodontics; Dental pulp